Mammalian middle ear mechanics: A review - Ugarteburu, Maialen; Withnell, Robert H.; Cardoso, Luis; Carriero, Alessandra; Richter, Claus-Peter (Frontiers in Bioengineering and Biotechnology, 2022)
The middle ear is part of the ear in all terrestrial vertebrates. It provides an interface between two media, air and water. How does it work? In mammals, the middle ear is traditionally described as increasing gain due to Helmholtz’s hydraulic analogy and the lever action of the malleus-incus complex: in effect, an impedance transformer. The conical shape of the eardrum and a frequency-dependent synovial joint function for the ossicles suggest a greater complexity of function than the traditional view. Here we review acoustico-mechanical measurements of middle ear function and the development of middle ear models based on these measurements. We observe that an impedance-matching mechanism (reducing reflection) rather than an impedance transformer (providing gain) best explains experimental findings. We conclude by considering some outstanding questions about middle ear function, recognizing that we are still learning how the middle ear works.